Studies on piglet diarrhoea associated with enterotoxigenic escherichia coli and its control by vaccination - Supar . (Hemera Zoa, 1995)
Piglet neonatal diarrhoea occured in all the piggeries studied in Indonesia. Field studies demonstrated the prevalence of diarrhoea in all piggeries were at range from 13.4% to 43.7% with and average 24.7%. The majority of piglets with diarrhoea were in the first 2 weeks of life. Mortality of piglets were at rates between 12.2% to 31.6% with an average 17.9%. The distribution of piglet mortality preceded by diarrhoea recorded in an intensive study in a piggery G for a seven week period showed a high positive correlation with diarrhoea (r2 = 0.79; P